HUBUNGAN ANTARA KEJADIAN ANEMIA DENGAN AKTIVITAS FISIK DAN RIWAYAT PENYAKIT INFEKSI PADA SISWI KELAS XI SMA NEGERI 11 SEMARANG - Aulia Annisa; M. Zen Rahfiludin; Siti Fatimah Pradigdo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Anemia prevalence in girls in Indonesia in 2017 reached 22.7%. Anemia rate in Central Java 2017 shows that 50% founded anemia in adolescent girls. As a result of anemia in adolescent girls, among others, decreases adolescent activity, learning achievement and adolescent fitness thus inhibiting sports performance. The purpose of this study was to determine the relationship between the incidence of anemia with physical activity and the occurrence of infectious diseases in class XI students of SMA Negeri 11 Semarang. The study was observational with a cross sectional approach. The study population was all students of class XI 11 Semarang State High School with inclusion and exclusion criteria and N sample 64 students. The sampling method is Simple Random Sampling. The research instrument was the Cyanmethemoglobin method for HB levels and research questionnaires for physical activity and infectious diseases. Data analysis used is Rank Spearman, Chi Square and Contingency Coefficient. The results showed that 21.9% had anemia, 78.1% of their physical activity was mild and 56,2% had experienced an infectious disease. Rank Spearman test results showed no association between the incidence of anemia and physical activity (p = 0.749) and the results of Chi Square test showed there was a correlation between the incidence of anemia with infectious diseases (p = 0.012) with r value of 0.300 which means that the correlation is quite strong. It is recommended that students should pay more attention to the surrounding environment and foods that will be consumed which contain lots of nutrients.